Implementation of Fletcher-Reeves in the GOSPEL optimization package - Hanson, Clyde Russell, 1959- (The University of Arizona., 1989)
Implementation of the Fletcher-Reeves optimization strategy into the GOSPEL optimization package is examined. An explanation of the GOSPEL package is provided, followed by the presentation of the Fletcher-Reeves strategy. Performance of all strategies in the updated GOSPEL package are compared for nine test cases. A user manual for GOSPEL operation as well as the source code are also included.